Guyana : monitoring the situation of children and women - multiple indicator cluster survey 2014 (Bureau of Statistics GeorgetownGY, 2015)
Presents key indicators that are used to assess the situation of children, women and men in areas such as health, education, child protection, and HIV/AIDS. Provides a tool to monitor the progress towards national goals and global commitments aimed at promoting the welfare of children, including the Millennium Development Goals (MDGs)
Keywords: CHILDREN